Limited resources in clinical facilities: Experiences of nursing students during placements - Julia L. Mafumo; Maria S. Maputle (Curationis)
Background: Students need resources in the clinical areas to integrate theory and practice. When healthcare facilities have limited resources, students encounter momentous challenges that negatively affect their learning and supervision.